PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS X MIA 5 MAN 2 MODEL PEKANBARU - Humaira, Hanifah; Solfitri, Titi; ', Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is classroom action research which aims to improve the learning process and the result of learning mathematics by applying Discovery Learning (DL) model. The subject of this research were the second semester students of class X MIA 5 MAN 2 Model Pekanbaru academic year 2016/2017 consisting of 13 male and 17 female students. Instruments on this reserach constisted of syllabus, lesson plans and worksheets; and instruments of data collection which is observation sheets and the test result sheets. The function of observation sheet is to obtain data from the learning process and analyzed in a narrative descriptive, while the function of results sheet of the mathematics learning tests is to obtain the results of the study and analyzed in statistics descriptive. From narrative descriptive analysis can be seen that there was improvement of learning process from before action in cycle I to cycle II. From statistic deskriptive analysis can be seen an increase in the number of students who reach the minimum criteria of mastery learning. The learning result of the student experience an increase from the basic score the Cycle I and Cycle II. On the knowledge competence, from the basic score with percentage 36,67% experience improvement in Cycle I with percentage 50% and 70% in Cycle II. On the skills competence, the number of students who reach the minimum criteria of mastery learning from Cycle I with percentage 23.33% improve to 50% in cycle II. Based on the results of this research can be concluded that the application of the Discovery Learning (DL) model can improve the learning achievement of the second semester students of class X MIA 5 MAN 2 Model Pekanbaru academic year 2016/2017.Key Words: Mathematics Learning Achievement, Discovery Learning model, Classroom Action Research